"Membaca" Televisi Indonesia, Sebuah Upaya Menyikapi Tayangan Televisi - Marfuah Sri Sanityastuti (Jurnal Komunikasi, 2007)
The television program in Indonesia has not beenfulfilling the basic character of a mass media yet It happens because there is no clear regulationfor broadcast, and no sufficient qualified human resources in this field. Since television program made without professionalism and creativity, then the content of television program does not represent the local culture. Instead, it made its own cultural reality. The society need to read (analyze) the television program as social phenomena. It can make them realize the positive and negative impact of television program on the society development. Society should know for sure the program they need, and the television station should accommodate this. In this case, television as a mirror of society should create the civilization which civilized and do it with dignity. It should be done, to build a constructive social development.